Does blended instruction enhance English language learning in developing countries? Evidence from Mexico. (5th May 2019) - Xu, Di; Glick, Danny; Rodriguez, Fernando; Cung, Bianca; Li, Qiujie; Warschauer, Mark
Abstract: Despite steady investment in English language education made by developing countries over the past few decades, results continue to be constrained by lack of high‐quality instructors and language learning resources. Thus, using technology in language instruction has increasingly been recognized as a potential approach for addressing these constraints. This study uses administrative data from a large public university in Mexico to examine the impact of a technology‐enhanced blended program on students' English course grades and course completion rates. Specifically, we focus on a campus‐wide policy change in all compulsory English language courses that replaces half of the traditional face‐to‐face class time with an interactive online learning environment developed by a leading technology‐mediated English language learning and assessment provider. Our results suggest that, compared to traditional face‐to‐face instruction, blended learning had a significant, positive impact on students' course grades and course completion rates. In addition, the enrollment‐teacher ratio increased after replacing half of the face‐to‐face instructional time with online learning, suggesting that blended learning environments hold promise for providing high‐quality and cost‐effective language instruction.